Hidup Selibat Sebagai Karunia Tuhan: Studi Eksposisi 1 Korintus 7:7 - Yosua Sibarani (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Everyone has a unique calling from God, including the call to life whether married or not. There is an assumption that celibacy is an unusual or abnormal life. On the other hand, celibacy is made an absolute requirement for an ordained priest in the Catholic church. The Bible upholds marriage, but it also teaches about the gift of celibacy (1 Cor. 7:7). This article aims to explain celibacy as a gift from God based on the study of the exposition of 1 Corinthians 7:7 and the theological implications for the lives of believers. For this reason, the author uses a qualitative method with a literature study approach. This article concludes that celibacy is a special gift from God for certain people. Finally, the implications of celibacy as a gift from God are that celibacy is not a curse or a disgrace, celibacy is not a matter of being more spiritual (holy) or not, and celibacy is not an absolute requirement to be a servant of God.